Application of the ultrafiltration-based LC-MS approach for screening PTP1B inhibitors from Chinese red yeast rice. Issue 2 (8th December 2015) - Jin, Yan; Cheng, Xueheng; Jiang, Faqin; Guo, Zheng; Xie, Jin; Fu, Lei
Abstract : Ultrafiltration-based affinity selection mass spectrometry was utilized to rapidly screen potential PTP1B inhibitors in Chinese red yeast rice. Abstract : Ultrafiltration-based affinity selection combined with liquid chromatography-mass spectrometry (LC-MS) is an efficient tool for screening complex mixtures, such as traditional medicines. And this approach has many advantages over the more conventional bioassay-guided isolation, which is time-consuming and laborious. This paper presents an application of an ultrafiltration-based LC-MS approach to screen potential protein tyrosine phosphatase 1B (PTP1B) inhibitors from Chinese red yeast rice (RYR), and the reliable potential active compounds were determined based on the optimized evaluation criteria of binding behavior. As a result, at least one compound in the RYR extract was identified as a potential PTP1B inhibitor, and its structure was confirmed to be that of monascorubramine using mass spectrometry elevated energy (MSE). The binding behavior of monascorubramine to T cell protein tyrosine phosphatase (TCPTP, a homolog of PTP1B) and other randomly chosen proteins (proprotein convertase subtilisin/kexin type 9, PCSK9; low-density lipoprotein receptor, LDLR; phosphomannomutase 2, PMM2; serine hydroxymethyltransferase, SHMT; bromodomain-containing protein 4 domain 1, BRD4-1; and jumonji domain-containing 2A, JMJD2A) was evaluated. RYR was verified to exhibit a selective PTP1B inhibitory activity, partially because monascorubramine showed selectivity towards PTP1B versus TCPTP and the other randomly chosen proteins.